Ameliorating effects of L-carnitine and synbiotic co-supplementation on anthropometric measures and cardiometabolic traits in women with obesity: a randomized controlled clinical trial - Fallah, Farnoush; Mahdavi, Reza (Frontiers in Endocrinology, 2023)
Background Obesity, a multifactorial disorder with pandemic dimensions, is conceded a major culprit of morbidity and mortality worldwide, necessitating efficient therapeutic strategies. Nutraceuticals and functional foods are considered promising adjuvant/complementary approaches for weight management in individuals with obesity who have low adherence to conventional treatments. Current literature supports the weight-reducing efficacy of pro/pre/synbiotics or L-carnitine; however, the superiority of the nutraceutical joint supplementation approach over common single therapies to counter obesity and accompanying comorbidities is well documented. This study was designed to assess the effects of L-carnitine single therapy compared with L-carnitine and multistrain/multispecies synbiotic co-supplementation on anthropometric and cardiometabolic indicators in women with obesity. Methods The current placebo-controlled double-blind randomized clinical trial was performed on 46 women with obesity, randomly allocated to either concomitant supplementation [L-carnitine tartrate (2 × 500 mg/day) + multistrain/multispecies synbiotic (1 capsule/day)] or monotherapy [L-carnitine tartrate (2 × 500 mg/day) + maltodextrin (1 capsule/day)] groups for 8 weeks. Participants in both groups received healthy eating dietary advice. Results Anthropometric, lipid, and glycemic indices significantly improved in both intervention groups; however, L-carnitine + synbiotic co-administration elicited a greater reduction in the anthropometric measures including body mass index (BMI), body weight, and neck, waist, and hip circumferences (p < 0.001, <0.001, <0.001, = 0.012, and =0.030, respectively) after adjusting for probable confounders. Moreover, L-carnitine + synbiotic joint supplementation resulted in a greater reduction in fasting blood sugar (FBS), insulin (though marginal), and homeostatic model assessment of insulin resistance (HOMA-IR) and more increment in quantitative insulin sensitivity check index (QUICKI; p = 0.014, 0.051, 0.024, and 0.019, respectively) compared with the L-carnitine + placebo monosupplementation. No significant intergroup changes were found for the lipid profile biomarkers, except for a greater increase in high-density lipoprotein-cholesterol concentrations (HDL-C) in the L-carnitine + synbiotic group (p = 0.009). Conclusion L-carnitine + synbiotic co-supplementation was more beneficial in ameliorating anthropometric indices as well as some cardiometabolic parameters compared with L-carnitine single therapy, suggesting that it is a promising adjuvant approach to ameliorate obesity or associated metabolic complications through potential synergistic or complementary mechanisms. Further longer duration clinical trials in a three-group design are demanded to verify the complementary or synergistic mechanisms. Clinical trial registration www.irct.ir, Iranian Registry of Clinical Trials IRCT20080904001197N13.